Ali so brezposelni motivirani za izobraževanje? - Radovan, Marko (AS. Andragoška spoznanja, 2003)
The author examines which factors influence motivation of the unemployed for education and learning. The main purpose of his research was to find out if their motivation is above all a reflection of individual manifestation of social pressures which "force" to or prevent from education. On the other hand, does motivation depend primarily on one's own motives, needs and expectations? The results of the research have shown that motivation for learning in the tested group of the unemployed is above all enhanced by the encouragement of reference groups and by self-efficiency. Educational intentions of individuals are influenced by social norms; they are connected with economic possibilities offered by their significant reference groups, as well as with encouraging to reach higher education levels. Self-efficiency is especially important for setting long-term educational goals (aspirations), and it is linked to the internal and external motivation of the unemployed for learning.
Keywords: izobraževanje odraslih; andragogika; Andragogy; brezposelni; brezposelnost; unemployment